1995
DOI: 10.1111/j.1365-2958.1995.mmi_18010045.x
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of inverted Ter sites into the terminus region of the Escherichia coli chromosome delays completion of DNA replication and disrupts the cell cycle

Abstract: To investigate the co-ordination between DNA replication and cell division, we have disrupted the DNA-replication cycle of Escherichia coli by inserting inverted Ter sites into the terminus region to delay completion of the chromosome. The inverted Ter sites (designated InvTer::spcr) were initially inserted into the chromosome of a delta tus strain to allow unrestrained chromosomal replication. We then introduced a functional tus gene by transforming the InvTer::spcr strain with a plasmid carrying the tus gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
74
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 39 publications
3
74
0
Order By: Relevance
“…Insight to the problem has been acquired through the examination of the consequences of stalling replication forks in vivo by various means. Placement of Ter sequences outside of the usual configuration at the terminus region of the chromosome generated strains that required RecA and RecBCD for survival if the replication-fork arrest protein Tus also was present (7,8). The models developed to explain these observations suggested that DSB formation was occurring at the stalled replication fork.…”
mentioning
confidence: 95%
“…Insight to the problem has been acquired through the examination of the consequences of stalling replication forks in vivo by various means. Placement of Ter sequences outside of the usual configuration at the terminus region of the chromosome generated strains that required RecA and RecBCD for survival if the replication-fork arrest protein Tus also was present (7,8). The models developed to explain these observations suggested that DSB formation was occurring at the stalled replication fork.…”
mentioning
confidence: 95%
“…If a newly initiated replication fork were to reach a stalled fork and copy nascent DNA at the stalled fork, this would create double-stranded ends, leading to a collapsed replication fork (6,32,47). Strains carrying DNA replication termination sites (Ter) at new positions in the chromosome depend on RecA, RecBC, and RuvABC (all proteins involved in recombinational repair) for viability (6,21, 0.47) Fork breakage was not evident in these cells, although linear DNA was created when a new fork reached a fork blocked at Ter.…”
mentioning
confidence: 99%
“…The nature of the stalled fork determines which proteins are involved in this process of fork reversal and replication restart. For example, RecA is required for RuvABC action when replication is arrested by inactivation of DnaB helicase (46), but RecA is not required when fork arrest is caused by the lack of Rep helicase (46) or a defect in the HolD subunit of the Pol III clamp loader (15) or in a dnaEts mutant (18).If a newly initiated replication fork were to reach a stalled fork and copy nascent DNA at the stalled fork, this would create double-stranded ends, leading to a collapsed replication fork (6,32,47). Strains carrying DNA replication termination sites (Ter) at new positions in the chromosome depend on RecA, RecBC, and RuvABC (all proteins involved in recombinational repair) for viability (6, 21, 0.47) Fork breakage was not evident in these cells, although linear DNA was created when a new fork reached a fork blocked at Ter.…”
mentioning
confidence: 99%
“…Similar dependence on RecA has been reported for E. coli strains with large chromosomal inversions (33) or ectopic termination blocks (18,49) or in cases of integrative suppression of oriC (36). Among all these RecA-dependent strains with diverse replication mechanisms from different origins (oriC, oripBR322, oriP2sig5, and oriR1), the only shared characteristic seems to be the prolonged arrest of replication forks at the Ter sites due to asymmetry in the overall chromosome replication.…”
Section: Discussionmentioning
confidence: 75%
“…It differs from the RuvAB-, RecBCD-, RecF-, or RecG-mediated mechanisms activated in E. coli when the replication forks are blocked because cells are deficient for the nonessential helicase Rep (47) or due to DNA lesions (6,38). It is also different from the recombinational rescue of strains with replication forks blocked at a Ter-Tus complex (17,18,49), which were described in terms of iSDR-type replication restart from a RecBCD-mediated D-loop structure (20). However, the TerTus systems used in these studies were not the natural arrest sites but rather a Ter site within the lac gene and an inverted Ter duplex cassette in the terminus region.…”
Section: Discussionmentioning
confidence: 97%